2021
DOI: 10.7717/peerj.11369
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects on development following microplastic exposure in Drosophila melanogaster

Abstract: Background Plastic pollution affects all ecosystems, and detrimental effects to animals have been reported in a growing number of studies. However, there is a paucity of evidence for effects on terrestrial animals in comparison to those in the marine realm. Methods We used the fly Drosophila melanogaster to study the effects that exposure to plastics may have on life history traits and immune response. We reared flies in four conditions: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…PETMNPL exposure has been reported to deteriorate fertility and result in a significantly smaller size of offspring [ 46 ], reduced oviposition in female flies, and lower triglyceride and glucose content in male flies [ 48 ]. Chronic exposure to PSMNPLs (1 μm and 20 nm) has recently been studied on Drosophila larvae by Matthews et al [ 47 ], who observed markedly impaired locomotor behavior, without any significant changes in survival, reproduction capacity, and egg-to-adult development in flies [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PETMNPL exposure has been reported to deteriorate fertility and result in a significantly smaller size of offspring [ 46 ], reduced oviposition in female flies, and lower triglyceride and glucose content in male flies [ 48 ]. Chronic exposure to PSMNPLs (1 μm and 20 nm) has recently been studied on Drosophila larvae by Matthews et al [ 47 ], who observed markedly impaired locomotor behavior, without any significant changes in survival, reproduction capacity, and egg-to-adult development in flies [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila melanogaster (fruit fly) has been used in various studies aiming to show the adverse biological effects (morphological changes, gut damage, phenotypic and behavioral effect, fertility, oxidative stress, gene expression and epigenetic effects, metabolic diseases, etc.) of different types of micro/nanoplastics [ 7 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Along with its ability to produce many generations in a short time (over 20 generations each year), D. melanogaster , on the other hand, allows scientists to circumvent common ethical restrictions placed on the use of higher vertebrates in experiments, namely, the principles of the three Rs: replacement, refinement, and reduction, which govern the treatment of laboratory animals [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PSMNPLs resulted in gut damage, locomotor dysfunction, epigenetic silencing, and aggravated cadmium toxicity, 14 as well as somatic mutation and recombination in the wing imaginal disks. 15 On the other hand, exposure to PETMNPLs was associated with changes in fertility, the offspring of treated flies were smaller than the offspring of controls, 16 as well as decreased oviposition in exposed females and reduction of triglyceride and glucose content in male flies. 17 In this context, the present study was planned to obtain information on a wide range of potential effects associated with exposure to PSMNPLs.…”
Section: Introductionmentioning
confidence: 99%
“…The use of insecticides may hormetically prime insect pests to become significantly more resilient to extreme circumstances by retaining stressful events. Several researchers have indicated that using insecticides at their sublethal dosages could lead to pest outbreaks 15 17 . The evolution of insecticide resistance in the vectors is a major failure cause of disease control programs 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of insecticides may hormetically prime insect pests to become significantly more resilient to extreme circumstances by retaining stressful events. Several researchers have indicated that using insecticides at their sublethal dosages could lead to pest outbreaks [15][16][17] 4 Institute of Plant Protection, Muhammad Nawaz Shareef University of Agriculture, Multan 60000, Pakistan. 5 Department of Plant Protection, Ministry of National Food Security and Research, Islamabad, Pakistan.…”
mentioning
confidence: 99%